Biological prostheses use for abdominal wall repair in open abdomen and incisional hernias: a single center results - Daniele Perrina; Carlo Vallicelli; Federico Coccolini; Massimo Sartelli; Belinda De Simone; Vanni Agnoletti; Luca Ansaloni; Fausto Catena (Academia Medicine)
Introduction: Biological prostheses (BPs) are a feasible option in abdominal wall reconstruction after open abdomen (OA) when primary fascial closure is not achievable or in treating abdominal wall hernias, especially in the presence of a potential or certain contaminated field. The present study reports the results of using a porcine dermal matrix for treating OA defects and incisional hernias, as extracted from the International Register of Biological Prostheses. Methods: Twenty-six consecutive patients treated in an emergency setting between July 2018 and March 2023 were analyzed. An acellular porcine dermal matrix was used. The mean follow-up period was 9 months. Statistical analysis was conducted using R (R Core Team, 2020). Results: At 1 year, 1 (3.8%) recurrence was reported, while no recurrence was observed at 1 month. Four patients (15.4%) developed an enterocutaneous fistula, and five patients (19.2%) experienced wound dehiscence. Subcutaneous drain placement was associated with a lower incidence of wound dehiscence (P = 0.042). The overall complication rate (including medical and surgical complications) was 61% at 1 month and 26.3% at 1 year. Conclusions: BPs are a feasible and effective option for reconstructing the abdominal wall after OA or incisional hernia in potentially or confirmed contaminated fields. Subcutaneous drain placement may help prevent wound dehiscence.